2013
DOI: 10.1016/j.humpath.2013.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and prognosis of duodenal adenocarcinoma and comparison with ampullary and pancreatic ductal adenocarcinoma

Abstract: Due to the rarity of duodenal adenocarcinoma (DAC), the clinicopathologic features and prognostication data for DAC are limited. There are no published studies directly comparing the prognosis of DAC to ampullary adenocarcinoma (AA) and pancreatic ductal adenocarcinoma (PDA) after resection. In this study, we examined the clinicopathologic features of 68 patients with DAC, 92 patients with AA and 126 patients with PDA, who underwent resection. Patient clinicopathologic and survival information were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…This figure is similar to the studies that focused on well-characterized cases of non-ampullary-duodenal carcinomas, where it is~55% with a range of 54-60% in the largest institutional series on this topic. 5,10,17,18 We found that the presence of gastric-pancreatobiliary histology may be associated with more aggressive behavior (although this did not reach statistical significance), which was also reported by others 10,16 and thus it is important to attempt to recognize and report this lineage (no matter the quantity) in any non-ampullary-duodenal carcinoma case.…”
Section: Months After Resectionsupporting
confidence: 48%
See 1 more Smart Citation
“…This figure is similar to the studies that focused on well-characterized cases of non-ampullary-duodenal carcinomas, where it is~55% with a range of 54-60% in the largest institutional series on this topic. 5,10,17,18 We found that the presence of gastric-pancreatobiliary histology may be associated with more aggressive behavior (although this did not reach statistical significance), which was also reported by others 10,16 and thus it is important to attempt to recognize and report this lineage (no matter the quantity) in any non-ampullary-duodenal carcinoma case.…”
Section: Months After Resectionsupporting
confidence: 48%
“…3 For non-ampullary-duodenal carcinomas, the literature reveals conflicting results, largely because they have often been analyzed with ampullary or other intestinal cancers. Recent studies are indicating that they may in fact be fairly similar to 'ampullary cancers', 4,5 but many of their characteristics have not been fully elucidated.…”
mentioning
confidence: 99%
“…However, in patients with a high risk for small bowel cancer (patients suffering from familial adenomatous polyposis (FAP) or Lynch syndrome (HNPCC)), a screening using EGD might be beneficial . Although no improvement in prognosis has been observed with (neo‐)adjuvant therapies, such as chemoradiation or chemotherapy, these additional therapies should be evaluated further because the prognosis of duodenal cancer is very dismal.…”
Section: Discussionmentioning
confidence: 99%
“…However, associations with hereditary or inflammatory conditions have been reported. [6,7] Periampullary adenocarcinoma is categorized into four types based on its origin: pancreatic adenocarcinoma, adenocarcinoma of the ampulla of Vater, distal bile duct adenocarcinoma, and DAC which represents the least common type. [2] Yeo et al identified 242 patients that underwent pancreaticoduodenal resection for periampullary adenocarcinoma from 1970 through 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DAC and AA had less frequent nodal metastasis and better prognosis than those with PDA, and the overall 5-year survival for DAC patients was 55.9%. [6] 4. CONCLUSIONS DAC is rare.…”
Section: Discussionmentioning
confidence: 99%